Multi-Wavelength Coherent-Perfect-Absorption−Laser Points and Half-Wave Phase Shift in Parity-Time-Reciprocal Scaling Symmetry Structure - Yongjun Xiao; Haiyang Hu; Xiaoling Chen; Junjie Dong; Dong Zhao; Fangmei Liu (Crystals, 2023)
Two slabs of dielectrics with different values of refractive index are synthesized to form a composite structure and the whole system satisfies parity-time-reciprocal scaling symmetry. Four coherent-perfect-absorber-laser points are induced by modulating the incident wavelength of lightwaves and the loss/gain factor of materials. The locations of coherent-perfect-absorber-laser points in parameter space, which manifests the multi-wavelengths of coherent-perfect-absorber-lasers could be regulated by the incidence angle. Especially, a value of π phase shift in the transmitted/reflected light wave has been observed as well. This research has potential applications in multi-wavelength absorbers/lasers and half-wave phase shifters.